2021
DOI: 10.1021/acscatal.1c02444
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism of MHETase, a PET Degrading Enzyme

Abstract: In 2016, one of the two enzymes involved in the polyethylene terephthalate (PET) degradation pathway of Ideonella sakaiensis 201-F6, MHETase, was found to exhibit a strong ability to degrade the PET monomer mono-(2-hydroxyethyl)­terephthalate (MHET) at room temperature, converting it back into the precursors used in PET production. MHETase engineering to improve efficiency is an active field that suffers from an incomplete characterization of its reaction mechanism. In this paper, we analyze the reaction mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 64 publications
(131 reference statements)
3
44
0
Order By: Relevance
“…In a previous work of Knott et al for MHETase, where they carried out QM/MM simulations at the SCC-DFTB:MM level, the authors suggested that the reaction occurred in two steps without the formation of stable tetrahedral intermediates. An alternative approach by Pinto et al , also for MHETase, at the B3LYP/GPW:MM level, indicated that the reaction mechanism obtained is analogous to that of canonical serine hydrolases, where the acylation and deacylation steps occur via a metastable tetrahedral intermediate. Here, we used a robust QM/MM umbrella sampling method, at the density functional theory level (PBE) with a larger QM region (146 atoms), and identified all its intermediates and transition states with high accuracy.…”
Section: Introductionmentioning
confidence: 92%
“…In a previous work of Knott et al for MHETase, where they carried out QM/MM simulations at the SCC-DFTB:MM level, the authors suggested that the reaction occurred in two steps without the formation of stable tetrahedral intermediates. An alternative approach by Pinto et al , also for MHETase, at the B3LYP/GPW:MM level, indicated that the reaction mechanism obtained is analogous to that of canonical serine hydrolases, where the acylation and deacylation steps occur via a metastable tetrahedral intermediate. Here, we used a robust QM/MM umbrella sampling method, at the density functional theory level (PBE) with a larger QM region (146 atoms), and identified all its intermediates and transition states with high accuracy.…”
Section: Introductionmentioning
confidence: 92%
“…To better summarize these elegant examples, the review is categorized into seven parts based on the monomers including threemembered ring monomers, four-membered ring monomers, five-membered ring monomers, six-membered ring monomers, seven-membered ring monomers, eight-membered ring monomers, and linear monomers, while some important materials such as PET and BPA-PC were not introduced in this review because they have been reviewed in great detail by others. [29][30][31][32][33][34] In the following, examples for achieving the polymerization-depolymerization cycle of the polymer are presented. By doing so, we aim to highlight the current and future studies in this rapidly growing and promising area.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently with this, the S214H mutant of IsPETase shows decreased activity when compared to the wild-type enzyme. 13 We note that there have been multiple elegant computational studies that have helped reveal the mechanisms of PET-degrading enzymes, [15][16][17][18] more global conformational changes involved in catalysis, 19,20 and contributed to associated engineering effort. [21][22][23][24] However, corresponding studies of the conformational dynamics of this catalytically important tryptophan remain limited.…”
Section: Introductionmentioning
confidence: 99%